Endometriosis Epigenetics - Kai, Kentaro; Nasu, Kaei; Aoyagi, Yoko; Narahara, Hisashi (Current Women's Health Reviews, 2018)
Background: The heritable silencing of genes, without a change in their coding sequence, is due to epigenetic mechanisms. These mechanisms involve DNA methylation, the modification of histone, and non-coding RNA. Disrupting the balance of the epigenetic profile or network can cause a variety of diseases. Objective: We provide an overview of epigenetic mechanisms and epigenetic modifiers in endometriosis, focusing on DNA methylation and histone modification. Results: We discuss the aberrant gene expressions induced by DNA methylation, histone modification, and epigenetic cross-talk in endometriosis, and we discuss these mechanisms in light of the hypothesis that endometriosis is an epigenetic disease. DNA methylation inhibitors and histone deacetylase inhibitors are approved as epigenetic drugs for other human diseases, which may contribute to the eventual use of epigenetic drugs for endometriosis. We discuss the possibility of applying these drugs in as treatment for endometriosis. Great potential is also suggested by the development of diagnostic tools and predictive and prognostic biomarkers that use the differences in epigenetic patterns between individuals with endometriosis and controls. We document the theoretical background of this concept. We also discuss some unresolved issues about epigenetic mechanisms in endometriosis, and we add our personal perspectives on the resolution of these issues. Conclusion: Recent findings on aberrant DNA methylation and histone modification in endometriosis support the hypothesis that endometriosis should be recognized, at least in part, as an epigenetic disease. However, further investigations are required to elucidate the complex interaction phenomena of epigenetics in endometriosis.
Keywords: epigenetics